Community-Based Digital Interventions to Combat Drug Abuse in Rural Areas: A Pilot Study in Central Java - Ismail, Ismail; Felecia, Felecia; Azizah, Anisa Kurniatul; Rahmawati, Diana (Westscience Press, 2025)
Illegal drug addiction remains a significant public health issue in rural areas, which has limited access to prevention and treatment services. This current research examines the possible of community-level digital interventions as a solution for rural drug abuse issues in rural Central Java. Using a qualitative design, the data were collected from in-depth interviews with six key informants like community leaders, health professionals, a digital literacy expert, and a former drug user. Thematic analysis identified that although digital interventions like online counseling, social media campaigns, and mobile apps have the potential for contribution, their success is hindered by low digital literacy, restricted internet access, cultural stigma, and lack of trust in digital platforms. The results underscore the need for community involvement, hybrid intervention models (blending online and offline) and localized content production to improve digital drug prevention efforts. The study concludes that for digital interventions to be effective in rural communities, they must be developed based on local socio-cultural contexts and integrated with existing community support systems.